THU0248 A Preliminary Report of Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcus (PANDAS) Related Maternal Autoimmunity. (9th June 2015) - Arslan Tas, D.; Gul Celik, G.; Kelle, B.; Tahiroglu, A.; Sakalli, H.
Abstract : Background: A subtype of obsessive-compulsive disorder (OCD) and tic disorders called as Pediatric Autoimmune Neuropsychiatric Disorders Associated with Streptococcus (PANDAS) is believed to be secondary to central nervous system (CNS) autoimmunity that occurs in relation to group A streptococcal infection. It is well-known that strepctococcal infections show familial tendency. Similarly, familial aggregation of OCD and tic disorders has been described in acute rheumatic fever and PANDAS. Also streptococal infections are frequently recognised to be the etiological factor in many autoimmune diseases. There may be similar involvement of immunological and genetic mechanisms in the PANDAS patients and their parents. Objectives: We would like to investigate the maternal frequency of autoimmune disorders in PANDAS. Methods: We evaluated 28 mothers of children formerly diagnosed as PANDAS an in the follow-up of Child and Adolescent Physchiatry Outpatient Clinic. History taking, physical examination, Anti-streptolysine O (ASO), antinuclear antibody, rheumatoid factor, pelvic X-ray and routine blood tests were performed. Results: Twelve of 28 mothers considered to have inflammatory back pain and sacroiliitis (radiographically). Fourteen mothers revealed high ASO levels (7 of them had sacroiliitis; which suggests poststreptococcic reactive arthritis). Six of them were diagnosed to have thyroid diseases and 8 of them were tested to have positive antinuclear antibody. Conclusions: PANDAS, a very rare childhood disorder, was hypothezed to have increased tendency of familial autoimmunity. This preliminary report may suggest the need for a more detailed family based genetic association research of these children for autoimmune diseases. References: Martino D, Defazio G, Giovannoni G. The PANDAS subgroup of tic disorders and childhood-onset obsessive-compulsive disorder. J Psychosom Res 2009;67(6):547-57. Murphy TK, Storch EA, Turner A, Reid JM, Tan J, Lewin AB. Maternal history of autoimmune disease in children presenting with tics and/or obsessive-compulsive disorder. J Neuroimmunol 2010;229(1-2):243-7. Disclosure of Interest: None declared